if nth term of an AP is (2n+1) find the sum of first n terms of AP

Asked by achalgoel | 9th Jan, 2010, 09:13: PM

Expert Answer:

an = a + (n-1)d = (2n+1) ...........(1)

Sn = n(2a +(n-1)d)/2

= n(a + (2n+1))/2

where a is the first term, which can be obtained by (1) by using n = 1.

a = 3

Sn = n(3 + (2n+1))/2 = n(n+2)

Regards,

Team,

TopperLearning.

Answered by  | 9th Jan, 2010, 11:12: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.